Screening of potential strain for bioprotein production from coconut dregs - Hafiza, Shukor; Ahmad Anas, Nagoor Gunny; Nor Hidayah, B. (IACSIT Press, Singapoore, 2012)
Link to publisher's homepage at www.iacsit.org/